Rice Hull Management System: A Mobile-based Application Tool for Cooperatives - Usita, Maricris; Timalog, Cris Ann Fogusa; Javier, Maychiel; Indap, Jhune Carlo; Calera, Gricelyn; Ramos, Jessa Jane (Bina Nusantara University, 2025)
This study focuses on the design and thorough assessment of the Rice Hull Management System RHMS for mobile devices, which targets cooperatives located specifically in Occidental Mindoro, Philippines. The Philippines is well-known for its rice production; however, there are severe concerns regarding environmental sustainability due to the poor management of rice hulls. To offer a solution, the Rice Hull Management System mobile application was created for user cooperatives from Occidental Mindoro. The application was developed using the RAD methodology with React Native and Firebase, enabling the system to be responsive, scalable, and secure. Through the utilization of RHMS, rice hull transactions are processed more efficiently with automated summaries, precision reports, advanced analytics, and real-time updates, all of which facilitate information-based decision-making and foster eco-friendly agricultural practices within and outside the region. The implementation evaluation of the system was conducted using a combination of surveys, usability tests, and performance benchmarks, which included IT specialists, cooperative staff, and members. System reliability was demonstrated to be high, with a Cronbach’s alpha greater than 0.80 and high user satisfaction, with grand mean scores ranging from 4.08 to 4.23 (“Very Good”). Evaluated criteria for the RHMS included efficiency, integration, usability, reliability, safety, and mobility, all of which received excellent ratings, confirming the system's effectiveness in resolving operational manual inefficiencies and enhancing transparency. This study focuses on the application of technology in rice hull waste management to promote environmental sustainability while meeting the requirements of agricultural cooperatives. The RHMS showcases considerable promise for development and implementation across agricultural supply chains, given its secure, easy-to-use, and flexible interface for users, administrators, and cooperatives. Proposed recommendations included continuous system enhancements, compliance with health regulations, integration with other platforms, and training programs to foster sustained system utilization and impact.